KESIMBA: A Game-Based Learning Approach to Teaching Malay Idioms in Primary Schools - Yusri Abdullah; Mohammad Zaimizan Zainal; Mohd H. A. Rahman; Fizaril Amzari Omar; Abu Bakar Ibrahim (LP3kM Buddhi Dharma University, 2026)
This study reports on the development and evaluation of KeSimba (Kembara Simpulan Bahasa), a digital game designed to enhance Year 5 pupils’ comprehension and motivation in learning Malay idioms (simpulan bahasa). Recognising pupils’ persistent challenges in mastering figurative language, the study aimed to identify the pedagogical need for a game-based approach, develop KeSimba using the ADDIE instructional design model, and evaluate its effects on idiom learning achievement and motivation. A mixed-method design involving 30 pupils and three Malay language teachers was adopted, employing a needs survey, pre- and post-tests, the System Usability Scale (SUS), and semi-structured teacher interviews. Findings indicated significant improvement in pupils’ idiom achievement, with mean scores increasing from 52.1 to 78.2, and an SUS score of 82.3 categorised as “Excellent”. Thematic analysis revealed three themes; heightened participation, enhanced confidence and transfer of learning, and the need for integration support. Grounded in Constructivism and Self-Determination Theory, KeSimba fostered contextual meaning-making, autonomy, competence, and relatedness. The findings suggest that culturally relevant, game-based tools can revitalise idiom learning when embedded in curriculum practices and supported through teacher training.